Multicausality of dengue in the North Coast of São Paulo: looking at the territory and listening to those who live in it (Terr@ Plural, 2022)
This article results from a broader study on dengue fever in the Northern Coast of São Paulo, a region whose urbanization process and unequal access to housing and urban services, such as sanitation, have triggered the emergence and return of several diseases. The categories of geographic space and psychosphere of Milton Santos are used to contextualize the health-disease process and the way individuals view daily life. The objective is to explicit the view of dwellers of Litoral Norte Paulista, who contracted dengue between 2002 and 2017, about the disease in their living spaces. This is quanti-qualitative research supported by data from the Ministry of Health, IBGE, and information obtained in interviews, applying the method of saturation and content analysis. The results show the vision of the participants about the process of becoming ill and the treatment of dengue. In conclusion, it highlights the importance of looking not only at the clinical state but also at the living space, since the roots of the main public health problems in Brazil are deep and based on conditions of our unequal social formation.
Keywords: Public health. Arbovirus. Cities. Environmental sanitation. Multifactorial causality.